Self Concept dan Subjective Wellbeing dalam Online Disinhibition Effect Mahasiswa Pengguna Instagram - Devinita Budiman; Hetti Sari Ramadhani; Adnani Budi Utami (JIWA: Jurnal Psikologi Indonesia, 2025)
Devinita Budiman Hetti Sari Ramadhani Adnani Budi Utami devinitaa28@gmail.com Abstract The Relationship Between Self-Concept and Subjective Well-Being with Online Disinhibition Effect Among Instagram Users. The purpose of this study is to analyze the relationship between self-concept and subjective well-being with online disinhibition effect among students who have Instagram accounts. This study employs a quantitative correlational approach, utilizing purposive sampling for sample selection and the Lameshow formula to determine the sample size in this population. Data were collected through an online questionnaire distributed across several social media platforms. A negative relationship was found between self-concept and the online disinhibition effect. The second hypothesis was accepted, indicating a significant negative relationship between subjective well-being and the online disinhibition effect. The results of this study showed a significant relationship between self-concept and subjective well-being with the online disinhibition effect among college students with Instagram accounts, with an F value of 93.48 and significance of 0.000 (p<0.05). This study concludes that self-concept and subjective well-being act as predictors of the online disinhibition effect among Instagram-using students. It is important for students to better understand themselves and enhance their awareness in maintaining appropriate behavior on social media, especially for those with multiple accounts, to avoid inappropriate behavior. Keywords: Online Disinhibition Effect, Self Concept, Subjective Wellbeing, Instagram Abstrak Hubungan Konsep Diri dan Kesejahteraan Subjektif dengan Efek Disinhibisi Online pada Mahasiswa Pengguna Instagram. Tujuan penelitian ini yakni guna menganalisis hubungan antara self concept dan subjective wellbeing dengan online disinhibition effect pada mahasiswa yang memiliki akun Instagram. Studi ini menggunakan pendekatan kuantitatif korelasional dengan menerapkan teknik purposive sampling untuk pengambilan sampel serta penggunaan rumus Lameshow untuk menentukan jumlah sampel pada populasi di penelitian ini. Data dikumpulkan berdasarkan kuesioner yang disebarkan secara online dibeberapa platform media sosial. hubungan negatif antara self concept dan online disinhibition effect. Hipotesis kedua diterima, yaitu terdapat hubungan negatif yang signifikan antara subjective wellbeing dan online disinhibition effect. Hasil penelitian ini menunjukkan adanya hubungan yang signifikan antara self concept dan subjective wellbeing dengan online disinhibition effect pada mahasiswa yang memiliki Instagram dengan nilai F sebesar 93,48 dengan signifikansi 0,000 (p<0,05). Penelitian ini menyimpulkan bahwa self concept dan subjective wellbeing berperan sebagai prediktor online disinhibition effect pada mahasiswa pengguna Instagram. Penting bagi mahasiswa untuk lebih mengenali diri dan meningkatkan kesadaran dalam menjaga perilaku di media sosial, terutama bagi mahasiswa yang memiliki akun ganda, guna menghindari perilaku yang tidak sesuai. Kata kunci: Online Disinhibition Effect, Self Concept, Subjective Wellbeing, Instagram